Factors Affecting Consumers’ Decision for E-Hotel Booking - Syed, Ayesha Ayub; Suroso, Jarot (Bina Nusantara University, 2018)
With more accessibility to the Internet and modernization of e-payment systems, the approach to address the travel requirements has dramatically changed over the years. The service offered by the Online Travel Agents (OTAs) has a huge impact on a very competitive online marketplace. The purpose of this research is to observe, examine, and analyze key factors which a consumers’ decision to use a particular travel agent website for e-hotel booking can be predicted. The data are compiled using IBM SPSS. The key methods are applied for data analysis in addition to other statistical methods including factor analysis and multinomial logistic regression analysis. The analysis of data reveals a positive association of website quality factors, product related factors, and consumer relationship factors with consumers’ decision to book from a certain travel agent website. Viewing the big picture, consumer relationship factors are found to be more influential as compared to website quality and product related factors. Moreover, the researchers reveal product price as the most influential variable, but it indicates no statistical significance with consumers’ decision. There are many different price products which are available across different travel agent websites. The convenience of payment method is found to be a significant attribute associated with the consumers’ decision to book from a travel website. In addition, attributes of travel products variety and online reviews provided by the travel websites are observed to be statistically significant. This research indicates the trends of consumer decision-making for e-hotel booking in Indonesia.